A glance at mathematical modeling from an ecological perspective: the problem of "Pine Processionary Caterpillar Invasion". (18th October 2022) - Çibik, Naz Fulya; Boz-Yaman, Burçak
Abstract: The purpose of this paper is to integrate mathematical modeling and ecology by presenting an activity involving an authentic environmental problem, which is called "Pine Processionary Caterpillars Invasion." Adopting Mathematical Modeling and Education for Climate Action (EfCA) approaches, it was aimed to encourage pre-service teachers (PSTs) to use the power of mathematical modeling processes to make inferences from data and evidence and make informed decisions by producing action plans to solve an ecological problem caused by climate change. The study was conducted with eight pre-service mathematics teachers and eight pre-service science teachers in a public university in Turkey. All PSTs worked as groups so that their mastery and thinking styles enriched each other. At the end of the activity, we noticed that some of the pre-service teachers confronted difficulties such as coming up with a working mathematical model, collecting real-world data from the pine forests, and efficiently computing steps of mathematical modeling without any errors. However, pre-service teachers could make use of the views of their working partners having different disciplines and appreciated the usefulness of mathematical modeling to solve an ecological problem. They also realized the interconnectedness of species and developed empathy for the welfare of society and nature.